Assessing Desertification Using Geospatial Techniques and Spectral Indicators During the Years 2015-2025 (Sabratha Municipality as a Case Study) (Al-Farooq Journal of Sciences, 2026)
This study aimed to monitor and assess desertification in the municipality of Sabratha, Libya, by determining the extent of its spatial and temporal changes using remote sensing and geographic information systems (GIS). The research problem lies in the noticeable acceleration of vegetation cover loss, soil aridity, and exposure resulting from climate change and human activities. This study established a continuously updated geographic database and made its findings and recommendations available to support decision-making in developing effective strategies and programs for land protection, rehabilitation of degraded land, and mitigation of desertification.The methodology relies on analyzing a time series of satellite imagery from the Landsat 8-9 OLI satellite and digitally processing it to extract three main spectral indices: the Normalized Difference Vegetation Index (NDVI) to measure the density and health of vegetation cover, the Normalized Moisture Index (NDMI) to estimate the moisture content in plants and soil and detect drought, and the Bare Soil Index (BSI) to distinguish degraded and barren land areas. These indices are then integrated using spatial analysis tools within the ArcGIS software environment to produce a thematic map showing the classification of desertification degrees in the region. The study indicated the efficiency of using spectral indicators in studying desertification, due to their ease of use and low cost. It also indicated the presence of four categories of desertification in the study area: severe, moderate, mild, and non-desertification, and the absence of the very severe desertification category in the two study views. The study also indicated, based on the change detection method and extracting the difference between time periods, an increase in the positive change category, such as a decrease in the area of ​​both vegetation cover and soil moisture, in contrast to an increase in the area of ​​bare soil in the year 2025 compared to the year 2015. Deforestation, overgrazing, urban expansion, and unsustainable exploitation of agricultural lands are the most prominent causes of desertification in the region.
Keywords: Desertification, Geospatial Technologies, NDVI, NDMI, BSI, ArcGIS.